Marathon progress: demography, morphology and environment - Marc, A.; Sedeaud, A.; Guillaume, M.; Rizk, M.; Schipman, J.; Antero-Jacquemin, J.; Haida, A.; Berthelot, G.; Toussaint, J.-F. (Journal of Sports Sciences, 2014)
As opposed to many other track-and-field events, marathon performances still improve. We choose to better describe the reasons for such a progression. The 100 best marathon runners archived from January 1990 to December 2011 for men and from January 1996 to December 2011 for women were analysed. We determined the impact of historical, demographic, physiological, seasonal and environmental factors. Performances in marathons improve at every level of performance (deciles). In 2011, 94% of the 100 best men athletes were African runners; among women athletes they were 52%. Morphological indicators (stature, body mass and Body Mass Index (BMI)) have decreased. We show a parabolic function between BMI and running speed. The seasonal distribution has two peaks, in spring (weeks 14 to 17) and autumn (weeks 41 to 44). During both periods, the average temperature of the host cities varies close to optimal value for long distance race. African men and women runners are increasingly dominating the marathon and pushing its record, through optimal eco-physiological conditions.